2023
DOI: 10.3390/ijms241411534
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor Heterogeneity and Treatment Resistance of Solid Tumors with a Focus on Polyploid/Senescent Giant Cancer Cells (PGCCs)

Abstract: Single cell biology has revealed that solid tumors and tumor-derived cell lines typically contain subpopulations of cancer cells that are readily distinguishable from the bulk of cancer cells by virtue of their enormous size. Such cells with a highly enlarged nucleus, multiple nuclei, and/or multiple micronuclei are often referred to as polyploid giant cancer cells (PGCCs), and may exhibit features of senescence. PGCCs may enter a dormant phase (active sleep) after they are formed, but a subset remain viable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 90 publications
3
17
0
Order By: Relevance
“…This was consistent with the hypothesis that evasion of apoptosis might This commentary highlights laboratory and clinical studies that have revealed the dark side of apoptosis in the context of cancer therapy and is meant to be complementary to recent reviews by pioneers in the field of regulated cell death [14][15][16]. Similar to our previous reports (e.g., [10,11]), the conclusions drawn from the studies outlined herein pertain to solid tumors/tumor-derived cell lines which may or may not be applicable to hematologic malignancies.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was consistent with the hypothesis that evasion of apoptosis might This commentary highlights laboratory and clinical studies that have revealed the dark side of apoptosis in the context of cancer therapy and is meant to be complementary to recent reviews by pioneers in the field of regulated cell death [14][15][16]. Similar to our previous reports (e.g., [10,11]), the conclusions drawn from the studies outlined herein pertain to solid tumors/tumor-derived cell lines which may or may not be applicable to hematologic malignancies.…”
Section: Introductionsupporting
confidence: 88%
“…Unfortunately, after decades of extensive research and clinical trials, novel apoptosistriggering therapeutic strategies under the term "precision oncology" still remain to fulfill their promises (reviewed in, e.g., [2][3][4][5][6][7][8][9][10][11]). In fact, a brief review of the history of cancer research has revealed that modern strategies for treating patients with certain types of solid tumors (e.g., esophageal cancer) may cause more harm than benefit (reviewed in [10]).…”
Section: Introductionmentioning
confidence: 99%
“…2,19 Moreover, recent evidence suggests that PGCCs senesce and produce cytokines that stimulate proliferation of neighboring cells. 130132 Our similar findings for experimentally-induced endocycling cells suggest these properties are inherent to an unscheduled endocycle state that is independent of other genetic and cellular complexities of human tumors. The similarity to iECs at wound sites suggests that unscheduled endocycles are another example that supports the perspective that tumors are like “wounds that do not heal”.133,134…”
Section: Discussionsupporting
confidence: 55%
“…A subset of cancer cells with a chaotic genome are readily distinguishable from the bulk of cancer cells by virtue of their enormous size and massive nuclear contents (i.e., a highly enlarged nucleus, multiple nuclei, and/or multiple micronuclei). These so-called polyploid giant cancer cells (PGCCs) can enter a state of transient dormancy (active sleep) after they are formed, but remain viable, secrete growth promoting factors, and exhibit the ability to undergo depolyploidization as well as "neosis" (nuclear budding and bursting), ultimately giving rise to stem-cell-like progeny that repopulate the tumor (reviewed in [25]; also see Figure 4). REVIEW 6 the ability to undergo depolyploidization as well as "neosis" (nuclear budding and bursting), ultimately giving rise to stem-cell-like progeny that repopulate the tumor (reviewed in [25]; also see Figure 4).…”
Section: Therapy-induced Dormancy Via Polyploidy/multinucleationmentioning
confidence: 99%
“…These so-called polyploid giant cancer cells (PGCCs) can enter a state of transient dormancy (active sleep) after they are formed, but remain viable, secrete growth promoting factors, and exhibit the ability to undergo depolyploidization as well as "neosis" (nuclear budding and bursting), ultimately giving rise to stem-cell-like progeny that repopulate the tumor (reviewed in [25]; also see Figure 4). REVIEW 6 the ability to undergo depolyploidization as well as "neosis" (nuclear budding and bursting), ultimately giving rise to stem-cell-like progeny that repopulate the tumor (reviewed in [25]; also see Figure 4). The mechanisms of formation and fate of PGCCs as well as their prevalence and prognostic value across different cancer types are well established and extensively discussed, albeit by only a handful of authors who reply on time lapse microscopy and other single cell assays (e.g., [59][60][61][62][63][64][65][66][67]).…”
Section: Therapy-induced Dormancy Via Polyploidy/multinucleationmentioning
confidence: 99%